ANALISIS NILAI RELIGIUS PADA LIRIK LAGU DALAMALBUM KHAZANAH SHALAWAT KARYA USTAZ JEFRI AL BUCHORI - Harbeng Masni; Brevenda Yulia Akmal (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2022)
Literature is inseparable from the values that exist in human life. Religious values play an important role in the life of religious people. This study aims to describe the religious values of the relationship between humans and God (Hablumminallah) in the Song Lyrics in ustaz Jefri Al Buchori's Khazanah Shalawat Album. This research uses a descriptive, qualitative method, which is to describe religious values. The source of this research data is the Song Lyrics in Ustaz Jefri Al Buchori's Khazanah Shalawat Album. Data analysis techniques are analyzing, interpreting, and drawing conclusions. As for the results of the analysis, it can be concluded that the religious values related between humans and God in the Song Lyrics in Ustaz Jefri Al Buchori's Khazanah Shalawat Album cover four aspects and seventy-one quotes are found in the Song Lyrics in Ustaz Jefri Al Buchori's Khazanah Shalawat Album, among them, (1) Thirteen citations are found in the aspect of faith,  (2) Twenty-one quotations are found on the aspect of worship, (3) Two quotations are found on the aspect of gratitude and (4) Three quotations are found on the aspect of being patient.